Essays in the eonomics of education in Brazil - Lepine, Andrea Gruenwald (2016)
This thesis is composed by three independent essays in economics of education, which aim to assess the impact of different public policies in Brazil. The first chapter studies the effects of a government scholarship program for low-income college students, the Prouni. Propensity score matching based on observable student characteristics and a proxy for previous student performance is used to deal with selection effects. The results are robust across different specifications, and suggest that students who received a scholarship perform better and take less time to reach their final year of college than comparable students. The estimated effects are higher among students with full scholarships than for students with partial scholarships, indicating that the amount of aid received matters. Results also indicate that full scholarship recipients also have a lower probability of working while in college. The second chapter provides evidence on a large-scale pay for performance program in the state of São Paulo, which awarded group bonuses to school teachers and staff conditional on improvements in student performance. Results using a difference-in-differences and triple-differences framework show that the program had overall positive effects on student performance, although improvements vary across grades and subjects. Although it could be expected that free-riding effects increase with the number of teachers in schools, thereby limiting the impact of the program, this effect seems to be modest. Results also show that initially low-performing schools improved much more than the average. The third chapter analyzes whether the provision of information on school quality affects students\' school choices. More specifically, it explores whether the publication of grades obtained at a standardized high school test (the Enem) resulted in changes in enrollments in high- and low-performing schools. A sharp regression discontinuity design is used, taking advantage of the fact that an exogenous rule determined that only schools with a minimum number of test-takers would have their results published. The results show that the disclosure of school grades did not significantly affect enrollment decisions, in neither private nor public schools. The findings remain unchanged when controlling for the degree of competition faced by schools or their socio-economic environment.